Efficacy of Tung’s Acupuncture in Managing Mild to Moderate Myopia Among the Young Adults – A Study Protocol for Randomized Control Trial - S, NaveenKumar; A, Moovendhan; N, Mangaiarkarasi; M R, Monicaasun (Indian Journal of Integrative Medicine, 2025)
Background: Myopia (near-sightedness) is most common eye condition in which faraway objects look blurry but not with near objects. Age between six to eight years were mostly affected by myopia which develops rapidly after 13 to 16 years of old. Acupuncture corrects the imbalance of the organs and systems by stimulating the Qi in the meridians and body’s regulatory mechanisms. Tung’s acupuncture method is distinguished by its significant use of distant points, straightforward needling techniques, and a distinct set of non-channel points. This study aims to investigate the effect of Tung’s acupuncture in mild to moderate myopia among young adults. Method: This study adapts randomized controlled design. 100 Subject will be recruited using convenient sampling technique, and randomized into two group. The study group will undergo Tung’s acupuncture and controlled group will not receive any intervention but standard care. Acupuncture will be given 20 minutes once a day in the alternative week for about 7 weeks. The refractive error will be assessed using TAPCON kerato-refractometer KR8900, and visual acuity by use of Snellen chart. Results: The outcome variables are refractory error and visual acuity which will be assessed before and after the treatment. Based on the hypothesis, this intervention may positively affect the refractive error of myopia. Conclusion: The positive results will confirm effectiveness of Tung’s acupuncture in improving the visual acuity among mild to moderate myopia adults. Thereby, Tung acupuncture can be implemented in the regular clinical practice in managing the visual acuity among myopia patients.